Pectin derived from hydrolysis of ripe Kepok Kuning banana peel powder employing crude pectinases produced by Aspergillus niger - Kumoro, Andri Cahyo; Shinta Mariana,; Maurice, Tri Hanly; Hidayat, Jefri Pandu (Penerbit Universiti Kebangsaan Malaysia, 2022)
Banana fruits consumption generates about 35% weight of peel waste containing approximately 10.61 to 24 w/w% of pectin. Hence, improper banana peel waste management may induce various environmental and health issues. The objectives of this work were to study the effect of substrate concentration, pH, temperature, and duration on the yield of pectin extracted from enzymatic hydrolysis of banana peel powder. In this work, the crude enzymes were obtained via submerged fermentation of Kepok Kuning banana peel powder utilising Aspergillus niger and directly used without prior purification. Pectin extraction from banana peel powder was performed through hydrolysis using crude pectinases at various substrate concentrations (0.033 to 0.123 g/mL), pH (4.0 to 6.0), and temperature (40 to 70°C) for 180 min. The increase of extraction parameters enhanced the pectin yield to a maximum value and then declined. High substrate concentration, temperature, pH, and monomeric pectin compounds formation at long hydrolysis duration were found to reduce enzyme activity. A recommended extraction condition is using 0.103 g/mL substrate concentration, pH 5.0, and 55 °C for 120 min to achieve 10.80% weight yield. Commercial implementations of the results can be worthwhile in solving the environmental problem and enhance the economic value of pectin-rich fruit peels and other agricultural wastes.